miR-190b promotes colorectal cancer progression through targeting forkhead box protein P2 - Zhao, Qiang (Exp Ther Med, 2020)
microRNA-190b (miR-190b) is abnormally expressed in multiple types of cancer, however, its role in colorectal cancer (CRC) is largely unknown. In the present study, it was demonstrated that miR-190b expression was upregulated in CRC cell lines compared with the normal epithelial colon cell line. Knockdown of miR-190b decreased proliferation, colony formation and invasion, and increased apoptosis of CRC cells. Furthermore, forkhead box protein P2 (FOXP2) was predicted as a target of miR-190b and further validated by luciferase activity reporter assay and western blotting. Rescue experiments showed that knockdown of FOXP2 reversed the inhibitory effects of miR-190b inhibitor on the behavior of the CRC cell lines. Taken together, the present study demonstrated the oncogenic role of miR-190b in CRC through regulation of FOXP2 expression.